Building a Community–Academic Partnership to Expand Workforce Development in Underserved, High-Need/High-Demand Areas. (May 2023) - Ruffolo, Mary C.; Price, Daicia; Smith, Andrea
This case study highlights the partnership development between a large, urban, public, community-based behavioral health system and an academic program. Using principles of partnership building and facilitators that enhance partnership building, we describe the process of initiating, building, and sustaining the partnership. The Health Resources and Services Administration (HRSA) workforce development initiative was the primary catalyst for the partnership development. The public, community-based behavioral health system is located in an urban, medically underserved area and health care professional shortage area. The academic partner is a master in social work (MSW) program in Michigan. We assessed partnership development by using process and outcome measures that captured changes in the partnerships and in implementation of the HRSA workforce development grant. The goals of this partnership were to develop the infrastructure to support the training of MSW students, expand workforce skills in integrated behavioral health, and increase the number of MSW graduates who work with medically underserved populations. During 2018-2020, the partnership trained 70 field instructors, engaged 114 MSW students in HRSA field placements, and developed 35 community-based field sites (including 4 federally qualified health centers). The partnership provided training for field supervisors and for HRSA MSW students and developed new courses/trainings focusing on integrated behavioral health assessment/intervention practices, trauma-informed care, cultural awareness, and telebehavioral health practices. Of 57 HRSA MSW graduates who responded to a postgraduation survey, 38 (66.7%) were employed in medically underserved, high-need/high-demand urban areas. Partnership sustainability was helped by formal agreements, regular communication, and a collaborative decision-making approach.